Shetland in the shed - Baglio, Ben M.; Gregory, Jenny (New York : Scholastic, 2001)
When a friend goes into the hospital, Mandy and James take in his daughter Polly and her shetland pony, but the owners of Animal Ark Veterinary Clinic find they must teach her how to overcome a fear of horses.
"A little Apple paperback."
510
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Pets -- Juvenile fiction; Fear -- Juvenile fiction